Dukungan Sosial sebagai Faktor Protektif terhadap Stres Belajar di kalangan Pelajar SMA - Maliana Julia Saputri; Surawan Surawan (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
Academic stress is a psychological condition commonly experienced by high school students in response to demanding academic expectations. This study aims to analyze the relationship between social support and academic stress among students at SMA Nurul Ihsan in Palangka Raya. Utilizing a quantitative correlational approach, data were collected from 20 students using a four-point Likert scale questionnaire covering variables of social support and academic stress. Descriptive statistical analysis showed that the average score for social support was 30.25, while the average score for academic stress was 24.80. Pearson correlation analysis indicated a moderate negative relationship (r = -0.425; p < 0.05), suggesting that higher levels of perceived social support are associated with lower levels of academic stress. Peer support was identified as the primary source of social support, whereas support from family and teachers was found to be less optimal. These findings highlight the importance of strengthening effective and responsive social support systems to promote students’ psychological well-being in facing academic pressure.